Sustainable wheat production through synergistic application of phosphate solubilizers and reduced phosphorus fertilization - Sk Asraful Ali (The Indian Journal of Agricultural Sciences, 2026)
Phosphorus (P) is an essential macronutrient for wheat growth and productivity. However, indiscriminate use of P fertilizers poses environmental and economic challenges. To address this, a field study was carried out during the 2021-22 and 2022-23 rabi seasons at Pantnagar, Uttarakhand (India), to enhance phosphorus use efficiency through the combined use of humic acid (HA) and phosphate solubilizing bacteria (PSB) under reduced phosphorus fertilization. The experiment followed a factorial randomized block design with three phosphorus levels (control, 50%, and 100%, corresponding to 0, 30, and 60 kg of P2O5 ha-1) and four phosphate solubilizers (control, HA @ 10 kg ha-1, PSB biofertilizer @ 10 g kg-1 seed, and HA @ 10 kg ha-1 + PSB biofertilizer @ 10 g kg-1 seed). The 100% phosphorus treatment resulted in the highest plant height (94 cm), grain yield (5.39 t ha-1), and total phosphorus uptake (39.82 kg ha-1). However, the combined HA and PSB treatment with 50% phosphorus produced a grain yield (4.83 t ha-1) comparable to that of 100% phosphorus alone (4.99 t ha-1). The HA + PSB treatment significantly improved growth parameters, including tiller number, spikes m-2, and dry matter accumulation, by enhancing phosphorus availability through microbial activity and humic acid synergy. Economically, the 100% phosphorus dose gave the highest net return of ₹1,14,149 ha-1, 18.51% higher than 50% phosphorus and 28.83% over the control. Although HA increased costs due to dosage, PSB showed a superior net benefit-cost ratio (2.81). This integrated approach reduces phosphorus fertilizer use by half without compromising wheat yield, providing an economically viable and environmentally sustainable production strategy.